Association of Gremlin-2 gene polymorphisms with osteoporosis risk in Chinese postmenopausal women. Issue 4 (24th April 2020) - Feng, Yu; Zhu, Lei; Gu, Yong; Wang, Ling-Jun; Niu, Bing-Jie; Cai, Feng; Chen, Liang
Abstract: The Gremlin-2 (GREM2) plays crucial roles in modulating bone homeostasis through the bone morphogenetic protein-2 pathway. However, GREM2 gene variants in osteoporosis were less frequent in a Chinese population. Therefore, the present study recruited 310 patients with osteoporosis and 339 healthy postmenopausal women to assess the correlation of GREM2 gene polymorphisms with the risk of osteoporosis. Polymerase chain reaction (PCR) and Sanger sequencing were utilized to genotype samples. The results showed that GREM2 gene rs4454537, not rs11588607, polymorphism was significantly associated with an increased risk of osteoporosis in postmenopausal women. Moreover, stratified analyses indicated a significant association between rs4454537 polymorphisms and body mass index of <25 kg/m 2 . Additionally, the association between GREM2 rs4454537 polymorphism and clinical characteristics was assessed, which showed that this locus decreased the bone mineral density (BMD) in postmenopausal osteoporotic individuals. Furthermore, individuals with CC genotype appeared to have a higher GREM2 expression compared with those bearing the TT genotype of rs4454537 polymorphism. However, the genotype distribution of rs4454537 polymorphism showed no statistical difference between osteoporotic patients as a function of fracture status. In summary, GREM2 rs4454537 polymorphism decreases BMD and increases osteoporotic risk in postmenopausal women.